PENERAPAN WEBSITE E-COMMERCE GUNA MENINGKATKAN PENJUALAN BUDIDAYA IKAN DESA BUGEL KECAMATAN PADARINCANG - Kristiyanto, Arip; Rohmawati, Iroh; Andriansah, Zulfi; Ahmad, Imam (LPPM Universitas Nusa Mandiri, 2025)
Serang Regency, covering 170,341.25 ha and consisting of 29 districts, has great potential for aquaculture development, including freshwater, brackish water, and marine farming. The post-pandemic economic condition has affected freshwater fish farmers in Bugel Village, Padarincang District, with a significant decline in both seed and consumption fish sales—up to 80%. The current marketing system still relies on word-of-mouth and WhatsApp status, resulting in limited market access. This community service activity aims to enhance the marketing of fish farming products among P2MKP Tambakan partners. The main activities include developing a web-based e-commerce platform and conducting branding training for partners. The methods used consist of institutional and participatory approaches, discussions, and training sessions. The developed e-commerce system can be accessed through www.tambakanfish.com. Socialization and training were implemented to improve partners’ digital marketing capacity. From five partner respondents, there was a significant increase in understanding of the e-commerce system and product photography techniques, from an average pre-training score of 51.5 to 85.1 post-training. Additionally, sales turnover increased by 12% in October and 18% in November. The results indicate that digitalization supports improved marketing performance and sales. In the future, partnerships with government and private sectors are expected to expand marketing networks through local exhibitions and bazaars.